Amish of Birch Creek : An Unbroken Heart - Book 2 - Fuller, Kathleen (Nashville, Tennessee : Thomas Nelson, 2016)
"Joanna Schrock returns home after a long stint in a physical rehabilitation center, but everything is different. Her parents have died, her sister is married, and she is having to learn to walk again with the help of her crutches. The one thing that hasn't changed is Andrew Beiler. He is still trying to court her, to win her heart, despite the fact that she does not deserve his attention. After all, she should have been the one to die in that accident, not her parents. Andrew knows Joanna is worth fighting for, if only she could see it for herself"--
Keywords: Man-woman relationships -- Fiction; Accident victims -- Fiction; Bereavement -- Fiction; Forgiveness -- Fiction; Amish -- Fiction; Grief -- Fiction; Christian fiction; Romance fiction